Hate : why we should resist it with free speech, not censorship - Strossen, Nadine (Inalienable rights series, 2018)
We live in an era in which offensive speech is on the rise. The emergence of the alt-right alone has fueled a marked increase in racist and anti-Semitic speech. Given its potential for harm, should this speech be banned? Nadine Strossen's HATE dispels the many misunderstandings that have clouded the perpetual debates about "hate speech vs. free speech." She argues that an expansive approach to the First Amendment is most effective at promoting democracy, equality, and societal harmony. Proponents of anti-hate speech laws stress the harms that they fear such speech might lead to: discrimination, violence, and psychic injuries. However, there has been no rigorous analysis to date of whether the laws effectively counter the feared harms. This book fills that gap, examining our actual experience with such laws. It shows that they are not effective in reducing the feared harms, and worse yet, are likely counterproductive. Even in established democracies, enforcement officials use the power these laws give them to suppress vital expression and target minority viewpoints, as was the case in earlier periods of U.S. history. The solution instead, as Strossen shows, is to promote equality and societal harmony through the increasingly vibrant "counterspeech" activism that has been flourishing on U.S. college campuses and in some global human rights movements. Strossen's powerful argument on behalf of free expression promises to shift the debate around this perennially contentious topic. --